The Role Of Promotion Mix On Visiting Decisions On Galesong Beach Tourism Takalar Regency, South Sulawesi, Indonesia - Feky Reken; Nadya Nurlailya Ningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The role of the promotion mix is crucial to the survival of a company or organization. Through a mixture of promotions, companies can inform and influence consumer or customer decisions just as they do with a beach tour. As for this study, it aims to measure the role of the mix of promotions carried out by coastal tourism galeong on the decision of visiting tourists. This research uses descriptive qualitative methods. Data is collected through interviews and observations. The results of the research showed that the coastal tourism management made adjustments to the role of the promotion mix. This adjustment is made by leveraging digital media and establishing good relationships with people, governments and end-users.